Spin observables in an atomic CQE system - Tielas, Diego Alejandro (2013)
A cavity quantum electrodynamical Hamiltonian is solved to study spin observables, such as the orientation and fluctuations of the total spin and entropy, in a system of N two-level atoms placed in a resonant cavity. The eigenstates of the Hamiltonian are calculated, both exactly and approximately. We calculate the time evolution of spin observables such as spin and entropy squeezing. Conclusions are drawn about the validity of the approximations in the limit of a large number of atoms.